Partners matter: the psychosocial well-being of couples when dealing with endometriosis - Schick, Maren; Germeyer, Ariane; Böttcher, Bettina; Hecht, Stephanie; Geiser, Magdalena; Rösner, Sabine; Eckstein, Monika; Vomstein, Kilian; Toth, Bettina; Strowitzki, Thomas; Wischmann, Tewes; Ditzen, Beate (Health and quality of life outcomes, 2022)
Endometriosis is often associated with severe dysmenorrhea, pelvic pain and dyspareunia and has a high impact on daily life as well as sexuality. Quality of partnership positively influences the course of various diseases and ability to cope with emotional and physical distress. However, studies focusing on the male partners of endometriosis patients are rare, and even less is known about the reciprocal relationship in these couples. Therefore, this study aims to explore the interrelations in couples with endometriosis in matters of psychological distress, sexual and partnership satisfaction and social support.
Gesehen am 30.06.2022